Wave Generation by a Finite Baffle Array in Application to Beam-Forming Analysis - TASINKEVYCH, Yuriy (Archives of Acoustics, 2010)
Directional excitation of sound in an aperiodic finite baffle system is analyzed using a method developed earlier in electrostatics. The solution to the corresponding boundary value problem is obtained in the spatial-frequency domain. The acoustic pressure and normal particle velocity distribution in acoustic media can be easily computed by the inverse Fourier transform from their spatial spectra on the baffle plane. The presented method can be used for linear acoustic phased arrays modeling with finite element size and inter-element interactions taken into account. Some illustrative numerical examples presenting the far-field radiation pattern and wave-beam steering are given.